Factors Influencing Decision Making to Revisit Japan of the Thai Bangkokian Millennial Tourists during Public Holidays - SRIMUK, Nattada; CHOIBAMROONG, Therdchai; LEE-ANANT, Chayapoj; PANPENG, Vorada; THONGON, Wallop (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023, 2023)
Even though Japan encounters several tourism issues including an epidemic like COVID-19, Japan is still among the pioneering countries when it comes to opening its doors to tourists. Currently, Japan tour packages are drawing high attention from Bangkokian millennials who prefer to travel during Thai public holidays due to diverse reasons. Hence, this study focused on identifying tourism marketing mix factors that influence Thai Bangkokian millennial tourists during Thai public holidays. Two hypotheses were set up. A verified questionnaire was used to collect the data from targeted 400 samples, then the data were analyzed into percentage, mean, and standard deviation. Also, Exploratory Factor Analysis (EFA) and regression analysis were used to test hypotheses and identify relationships and influences between variables. The results indicated that, in terms of demographic characteristics, gender, age, status, occupation, and income influence Thai millennial tourists to revisit Japan. Meanwhile, according to 12 tourism marketing factors, product and service quality factor, price factor, promotion factor, process factor, political factor, performance management factor, and presentation and public relations factor significantly affect the decision to revisit Japan of Thai millennial tourists in the Bangkok during public holidays.